(3QCi GdEeGe LGHQ hGdEeGe NGdOs
(3ChdgG (B:s
(3CeG HYO aEfi QGjJ Hjf GdEeGe NGdO QVi Gddg Yfg hLGHQ Hf MjGf QMeg Gddg ai GdJOHjQ GdCYXe NdGakG aSCdJ Yfg SjOi GdTjN YHO GdeDef aCNHQfi Cf QCi NGdO QCi GdadGSaI GdbOeGA hQCi LGHQ QCi faSg s
(3BNQgG (B:s
(3hjSbi Hg hjOHQ ceG JbOe hjchf BfGA GdYbO GdPi dgPG eKbhH dJNQL efg GdQWhHI hGdYed bO UM Pdc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHY YTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs